The effect of interventionist dynamic assessment on Iranian EFL learners’ vocabulary learning and retention: a sociocultural inquiry - Malihe YarAhmadi; Hossein Kargar Behbahani (Language Testing in Asia)
Abstract Traditional approaches to language assessment have been criticized for their inadequacy in taking account of language learners’ potential for development. To obviate this pitfall in traditional assessment, language teachers and researchers have been paying increasing attention to dynamic assessment (DA), which is rooted in Vygotsky’s (1978) sociocultural theory (SCT). This study investigated the potential of the interventionist approach to DA in facilitating vocabulary learning and retention among Iranian English-as-a-Foreign-Language (EFL) learners. To this end, adopting a quantitative quasi-experimental pretest–posttest-delayed posttest control group design, 80 pre-intermediate learners from two intact classes from a university in South Iran were randomly divided into two conditions: an experimental group (EG), which received DA-based treatment with appropriate scaffolding and zone of proximal development (ZPD)-sensitive instruction; and a control group (CG), which, in contrast to the EG, received traditional vocabulary instruction with the teacher merely providing direct translation of the target vocabulary. Pretests, posttests, and delayed posttests were administered to measure the knowledge of the target vocabulary across the three time occasions. The conduct of an inferential multivariate test of significance demonstrated that the learners in both conditions had very limited baseline knowledge of the target words. However, the test of significance revealed that the ZPD-sensitive instruction significantly boosted the learners’ vocabulary learning and retention. This suggests that the interventionist approach to DA not only has short-term effects on vocabulary learning, but also facilitates vocabulary retention among Iranian university-level EFL learners. The implications of the study for various stakeholders in language pedagogy are discussed.